Electrical Resistivity Tomography Techniques for Identifying Groundwater Pollution Due To Leachate flows at Putri Cempo Landfill - Harjito, Harjito; Suntoro, Suntoro; Gunawan, Totok; Maskuri, M. (Proceeding International Conference on Science and Engineering, 2017)
Landfill developed with open dumping system and below the adequate standard potentially lead to new problems like those found at Putri Cempo Landfill in Surakarta City. They include leachate, which easily flows in runoff, seeps through soil and land surface, and infiltrate into groundwater that supplies the surrounding residential wells. A research on leachate spread pattern from landfills to their surrounding areas thereby becomes necessary particularly in terms of environmental pollution potential from underground, which is latent and difficult to monitor. The aims of this research were (1) to identify the areas that experienced groundwater pollution due to leachate flows, (2) to identify the distribution of resistivity in these areas, and (3) to develop a model for leachate management. This research used Electrical Resistivity Tomography (ERT) survey for identifying the distribution of resistivity in polluted areas. It also used groundwater quality analysis for validating the interpretation of the ERT survey results. The results of the research showed that there was an anomaly in the subsurface layer. Materials with resistivity values of 0.25-1.20 ohmm were found in various depths within 0-8 m below the surface. These values were much lower than the resistivity of the main materials found at the measurement site, i.e. 4.9-13.1 ohmm. Accordingly, this anomaly signified the existing influence of pollution. The pollution along the geoelectrical sounding line had uneven distribution and centric pattern at several points that indicated the accumulation sites of leachate. The proposed leachate management model included the constructions of base lining (liner), leachate collection channel, geomembrane-composed final cap, and leachate treatment.